2010
DOI: 10.1021/bi100074s
|View full text |Cite
|
Sign up to set email alerts
|

Proton Affinity of the Oxyanion Hole in the Active Site of Ketosteroid Isomerase

Abstract: The absorption spectra of a series of inhibitors bound at the active site of Δ5-3-ketosteroid isomerase from Pseudomonas putida were found to exhibit substantial variations in the contributions of the protonated and deprotonated forms. Systematic variation of the inhibitor solution pKa combined with a method of quantifying the contributions of each protonation state showed the oxyanion hole in the active site of wild-type Δ5-3-ketosteroid isomerase to have a proton affinity equal to a solution pKa of 10.05 ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
62
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(73 citation statements)
references
References 36 publications
11
62
0
Order By: Relevance
“…This series of spectra strongly suggests that single-ring phenols bind to the pKSI D40N mutant with a neutral phenol fraction that becomes significant at a phenol pK a greater than 8 and increases with the phenol pK a until the protonated phenol is the predominantly bound form at or above a pK a of 10. This conclusion is consistent with prior UV and IR studies (13,22), and it is further supported by 13 C NMR and IR results described below.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…This series of spectra strongly suggests that single-ring phenols bind to the pKSI D40N mutant with a neutral phenol fraction that becomes significant at a phenol pK a greater than 8 and increases with the phenol pK a until the protonated phenol is the predominantly bound form at or above a pK a of 10. This conclusion is consistent with prior UV and IR studies (13,22), and it is further supported by 13 C NMR and IR results described below.…”
Section: Resultssupporting
confidence: 92%
“…Recent spectroscopic studies suggested that single-and multiple-ring phenolic ligands are bound to pKSI D40N with a neutral, protonated fraction that increases with ligand pK a and reaches a ratio of 50:50 ionized/neutral for a ligand with a solution pK a of 9.7 (13,22). To dissect and understand the nature and properties of proton transfer within the KSI oxyanion hole, we turned to systematic studies with single-ring phenols, because these compounds are available over a wider pK a range than naphthols or steroids.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations